Experimental investigation of CoFe$_2$O$_4$ particle size and acoustic properties of magnetic fluid - Zieliński, Bartek; Skumiel, A.; Józefczak, A. (Archives of Acoustics, 2006)
In this paper magnetic particle size and acoustic properties of the ferrofluid with CoFe$_2$O$_4$particles are presented. The results acquired from atomic force microscope measurementswill let us set average value for the hydrodynamic diameter of magnetic particles appearing inCoFe$_2$O$_4$ ferrofluids. The knowledge of these sizes is extremely useful because on the furtherstage of examinations it allows us to determine the size of surfactant coating particles. It ispossible by making additional magnetic measurements enabling the size of average magneticcore contained in the ferrofluid. Also, it allows us to determine in a simple way the thicknessof the surfactant layer. Such information on magnetic particles in a given ferrofluid is veryvaluable in the context of the application of the liquids either in technology or in medicine.Moreover, ultrasonic measurements carried out are providing the valuable information for uson the subject of the ferrofluid stability exposed to the action of the external magnetic field.The experimental estimation of the ultrasonic wave absorption coefficient in the function of afield for a few temperatures allows us to forecast how magnetic particles in a given magneticliquid are capable of joining together and creating clusters, and how big aggregates can becreated in this way.